Chemical Profile of the Sulphated Saponins from the Starfish Luidia senegalensis Collected as by-Catch Fauna in Brazilian Coast - Pereira Tangerina, Marcelo Marucci [UNESP]; Cesario, Julia Pizarro [UNESP]; Raggi Pereira, Gerson Rodrigues [UNESP]; Costa, Tania Marcia [UNESP]; Valenti, Wagner Cotroni [UNESP]; Vilegas, Wagner [UNESP] (Springer, 2018)
The by-catch fauna of the shrimp fishery includes a number of marine invertebrates that are discarded because they do not have commercial value. In order to try to add some value to these materials, we analyzed the chemical composition of the starfish Luidia senegalensis collected in the Brazilian coast as a consequence of the trawling fishery method. In order to access their chemical composition, we used a combination of solid phase extraction (SPE) followed by ultra-high performance liquid chromatography coupled to electrospray ionization ion trap tandem mass spectrometry (UPLC-ESI-IT-MSn). Luidia senegalensis contains asterosaponins, which are sulphated glycosilated steroids, containing five and six sugar moieties, in addition to polyhydroxysteroids. This study helped us to support the presence of important and potentially bioactive compounds in invertebrates associated to the by-catch fauna of the shrimp fishery, using a fast and efficient method. [GRAPHICS] .
Keywords: Luidia senegalensis; By-catch fauna; Asterosaponins; UPLC-MS